Towards the African Etymology of Greek ἔβενoς - Gábor, Takács (Polskie Towarzystwo Filologiczne, 2021)
This paper seeks the ultimate origin of our European term for ebony. The line of a number of borrowed forms has long been well known down to Egyptian, but all the problems surrounding the source of this term itself have so far not been subject to a careful investigation. First, we try to locate the Coptic reflex of Eg. hbnj in order to verify its supposed vocalisation. Secondly, all the diverse approaches to resolving its puzzling origin are critically evaluated. Thirdly, we present abundant linguistic evidence for an entirely new derivation from the ancestral Common Afro-Asiatic root stock itself with unavoidable implications on the mid-Holoce past of this oldest neolithic macrofamily.